Chinese overseas ports in Southeast and South Asia : cutting through the froth - Blanchard, Jean-Marc F., 1962- (Routledge, 2025)
"This book examines PRC "involved" seaports overseas, where involvement can take the form of PRC foreign direct investment (FDI), contracting, and/or terminal operations, in countries such as Cambodia, Pakistan, and the Philippines. Including country-oriented chapters the book sheds light on inter alia the realization (or not) of Chinese seaports, the effects of Chinese participation on port performance, trade, FDI, employment, and the environment, and the wider economic, political, and other ramifications of China's role. Importantly, the case studies in the book clearly demonstrate that amongst these ports there are successes and failures, positive or negative effects are not preordained, and domestic and international political factors notably influence what occurs in these overseas ports. The book also illuminates the critical role of 3rd parties (including India) in shaping the dynamics of China's participation in Southeast and South Asian ports and evaluate the potential for Chinese-involved ports to become naval bases. Presenting contributions from experts on Southeast and South Asia and utilising rich empirical data to reveal the factors that are driving China's participation overseas this book will appeal to students and scholars of Asian and Southeast Asian studies, international relations, particularly through the lens of economic relations"-- Provided by publisher.
Keywords: Harbors -- Southeast Asia.; Harbors -- South Asia.; Harbors -- China.; China -- Foreign economic relations.; China -- Relations.; elektronické knihy; electronic books